Manifestations of politeness and power in problem-solving business telephone calls - Irina S. Lebedeva; Evgeniya V. Ponomorenko (Peoples' Friendship University of Russia (RUDN University), 2023)
The article features some of the research findings obtained during an analysis of patterns of polite behaviour typical of subordinate and superior speakers in business telephone settings. The overall objective of the research was to describe how politeness manifests itself in opening, message and closing routines of business telephone calls and what factors play out in the choice of politeness strategies. The aims of the research presuppose the solution of the following research questions. Is there any discernible correlation between the degree of politeness and the social factor of power/social role in problem-solving business telephone interaction? Does the ranking of imposition affect the use of politeness? How does the setting affect politeness? What impact does the business telephone call environment and its restrictions have on patterns of polite behaviour? Are patterns of politeness different in different problem-solving call routines? The study is conducted within the framework of the lingua-pragmatic, socio-cultural and conversation analyses. The research methods include data collection, observation, quantitative analysis, comparative analysis, and evaluation. The corpus used for the analysis features samples of authentic problem-solving business telephone interaction which include transcripts of task-oriented calls made in the workplace. The materials have been obtained from the audio sections of Business English textbooks. The analysis reinforces assumptions about the heterogeneity of business telephone interaction. Manifestations of politeness show a lot of variability and dependence on a vast range of variables, including social (power / acquired social role, distance between the interactants, gender). The opening and closing routines of problem-solving calls are inherently formulaic and show the interactants' adherence to positive politeness. The message part is more task-oriented and structurally complex, hence the greater diversity of patterns of polite behaviour observed here.